Understanding outcomes and toxicological aspects of second generation metal-on-metal hip implants: a state-of-the-art review. (26th November 2018) - Kovochich, Michael; Finley, Brent L.; Novick, Rachel; Monnot, Andrew D.; Donovan, Ellen; Unice, Kenneth M.; Fung, Ernest S.; Fung, David; Paustenbach, Dennis J.
Abstract: Hip implants have improved the mobility and quality of life in millions of individuals. This review presents the evolution of scientific knowledge regarding the history and understanding of systemic and local metal toxicological concerns of hip implants designs utilizing metal-on-metal (MoM) bearing surfaces used in hip resurfacing arthroplasty (HRA) and total hip arthroplasty (THA). This analysis addresses: (1) the history of the development of MoM hip implants; (2) the clinical and toxicological rationale for introducing second-generation MoM implants in the early 2000s as an alternative to metal-on-polyethylene bearings; (3) the subsequent history regarding success and failure of second-generation MoM devices; (4) a detailed review of the history of MoM toxicology, including carcinogenic potential, metal blood levels, hypersensitivity, and release of wear particles; and (5) a review of local tissue effects and MoM patient management. We have included an analysis of MoM THA and HRA survivorship trends aggregated from over 200 studies. By around 2008, HRA continued to be a challenging procedure with variable success rates, and concurrently, some THA devices began to experience higher than expected revision rates based on annual registry reports. The unexpected THA outcomes and continued challenges with HRA devices prompted many surgeons to question the role of toxicological effects in device performance. Regarding hypersensitivity, while conversion to metal sensitized status in some MoM patients occurs based on the skin patch or lymphocyte transformation testing, there is no evidence of a causal relationship between positive test results and device failure. The weight of evidence indicates that nanoparticles released from MoM implants are cleared from the local synovial space under normal wear conditions. The available data indicate that there are no discernible increases in local or systemic tumors following CoCr alloy implantation. Systemic health effects are rarely reported in MoM implant patients and are unlikely when blood concentrations are below 300 µg/L except when patients have specific risk factors. Over time, patient management evolved to include assays aimed at predicting implant function (blood monitoring) and soft tissue reactions (MRI and ultrasound imaging). Validation of these biomarkers as a diagnostic tool for implant function, patient pain, and, ultimately, implant survival, remains lacking. After the introduction of these biomarkers, differences in implant revision decisions emerged based on imaging abnormalities, increased serum metal ion levels, and overall clinical presentation. Discrepancies in patient management algorithms and the lack of consensus in local biological effects terminology have contributed to variability in reporting incidence, etiology, and dose effects on local tissue responses in MoM implants. This variability has contributed to a debate regarding the benefit or risk of revising asymptomatic patients. Therefore, while toxicological assessments of normal functioning MoM implants indicate that MoM implants are relatively safe because of low wear and clearance of metal, more analysis of revision data is needed in order to best inform patient management decisions, particularly for asymptomatic patients, as well as patients with minor symptoms under consideration for conservative pain management treatments.